Determining the best recovery option under different corporate objectives via fuzzy based MCDM techniques - KILIÇ, HÜSEYİN SELÇUK; KALENDER, ZEYNEP TUĞÇE (My University, 2024)
Creating a closed-loop economy by recycling used products is of great importance in terms of ensuring economic and environmental sustainability. In order to maximize the benefit obtained from the recovery process, it is necessary that the products are included in the system according to the most suitable recovery option. One of the most important product types within the scope of the recycling process is rental products, which are covered in this study. Due to the nature of rental products, entering the recycling process frequently makes the need to determine the most suitable recovery option even more important. In the relevant decision process, one of the situations encountered in practice is that different departments of the institutions have different purposes. The values of recovery options may differ according to the relevant purposes. With this study, it is aimed to present a structure where scores can be generated for each recovery option, taking into account the objectives of different departments. In this structure, Spherical Fuzzy AHP (SF-AHP) and Spherical Fuzzy TOPSIS (SF-TOPSIS) from fuzzy Multi-Criteria Decision Making (MCDM) techniques are used in an integrated manner. To demonstrate the validity of the presented approach, an application was made on leased modems in one of Turkey\"s major telecommunications companies. All possible scenarios have been analyzed and interpreted from various perspectives under different department weights and different situations that the criteria may take. Thus, the effects of the department goals on the criteria were observed and their effects on the decisions could be examined numerically.

Kullanılmış ürünlerin geri kazanılarak kapalı döngü bir ekonomi oluşturulması, ekonomik ve çevresel sürdürülebilirliğin sağlanması açısından büyük önem taşımaktadır. Geri kazanım sürecinden elde edilen faydayı maksimize etmek açısından en uygun geri kazanım opsiyonuna göre ürünlerin sisteme dahil edilmesi gerekmektedir. Geri kazanım süreci kapsamına giren en önemli ürün tiplerinden birisi de bu çalışma kapsamında ele alınan kiralık ürünlerdir. Kiralık ürünlerin doğası gereği geri kazanım sürecine sıklıkla girmesi, geri kazanım opsiyonlarından en uygun olanının belirlenmesi ihtiyacını daha da önemli hale getirmektedir. İlgili karar sürecinde, uygulamada karşılaşılan durumlardan birisi de kurumların farklı departmanlarının farklı amaçlar içermesidir. Geri kazanım opsiyonlarının değerleri ilgili amaçlara göre farklılaşabilmektedir. Bu çalışmayla farklı departmanların amaçlarının göz önünde tutularak her bir geri kazanım opsiyonu için skor üretilebilen bir yapı sunulması hedeflenmektedir. Bu yapıda bulanık Çok Kriterli Karar Verme (ÇKKV) tekniklerinden Küresel Bulanık AHP (KB-AHP) ve Küresel Bulanık TOPSIS (KB-TOPSIS) bütünleşik bir şekilde kullanılmıştır. Sunulan yaklaşımın geçerliliğini göstermek için Türkiye’nin büyük telekomünikasyon şirketlerinden birinde kiralık modemler üzerinde uygulama yapılmıştır. Farklı departman ağırlıkları ve kriterlerin alabileceği farklı durumlar altında olası bütün senaryolar çeşitli açılardan analiz edilmiş ve yorumlanmıştır. Böylece departman hedeflerinin kriterler üzerindeki etkileri gözlemlenmiş ve kararlar üzerindeki etkileri sayısal olarak incelenebilmiştir.
Farklı kurumsal amaçlar altında bulanık ÇKKV tekniklerine dayalı en iyi geri kazanım opsiyonunun belirlenmesi
Keywords: Sosyal ve Beşeri Bilimler; Sanat; İç Mimarlık; Mühendislik ve Teknoloji; Social Sciences and Humanities; Art; Interior Architecture; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sanat ve Beşeri Bilimler (AHCI); Mühendislik; Sanat ve Beşeri Bilimler; MİMARİ; Engineering, Computing & Technology (ENG); Arts & Humanities (AHCI); ENGINEERING; ARTS & HUMANITIES; ARCHITECTURE; Mimari; Fizik Bilimleri; Genel Mühendislik; Architecture; Physical Sciences; General Engineering; multi criteria decision making; Recovery options; rental products; SF-AHP; SF-TOPSIS; sustainability; Geri kazanım opsiyonları; kiralık ürünler; sürdürülebilirlik; çok kriterli karar verme; KB-AHP; KB-TOPSIS; Recovery options; rental products; sustainability; multi criteria decision making; SF-AHP; SF-TOPSIS